Kinematic analysis of li ya salto connecting straddled jaeger salto on the uneven bars - Liu, Y.; Zhou, J. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
He Kexin, called the "UB princess", is the only individual event grand slam winner on uneven bars of the Chinese Women's Gymnastics Team. Her special skill "Straddled Jaeger Salto with a 1/2 Turn to re-grasp HB (also called Li Ya Salto) connecting the Straddled Jaeger Salto" was videotaped and 3-D analyzed. The conclusive kinematic characteristics of this high skilled element can provide useful information for the technical training of coaches and athletes, and enrich gymnastic theories.